Inhibition of Inflammation, Suppression of Matrix Metalloproteinases, Induction of Neurogenesis, and Antioxidant Property Make Bryostatin-1 a Therapeutic Choice for Multiple Sclerosis - Safaeinejad, Fahimeh; Bahrami, Soheyl; Redl, Heinz; Niknejad, Hassan (Frontiers in Pharmacology, 2018)
Multiple sclerosis is a neurodegenerative disease characterized by inflammation and myelin damage. Pro-inflammatory cytokines, oxidative stress, high level of matrix metalloproteinases (MMPs) activity and blood-brain barrier (BBB) damage, immune-mediated destruction of myelin and neuron loss are involved in the pathogenesis of MS. The currently approved treatments for MS include injectable drugs (interferon-β and glatiramer acetate), oral drugs (fingolimod), and monoclonal antibodies (natalizumab). The mentioned therapeutic choices are mostly focused on the inhibition of inflammation. Therefore, the search for a multi-target therapeutic choice remains unchallenged. It seems that a drug with anti-inflammatory, oxidative stress inhibitory, reduction of MMPs activity, and neurogenesis stimulatory properties may be effective for treatment of MS. In this regard, Bryostatin-1 as a macrolide and marine natural product has been selected as a therapeutic choice. Studies indicate that Bryostatin-1 has anti-inflammatory and antioxidant properties and decreases MMPs level and BBB damage. Furthermore, Bryostatin-1 has a neuroprotective effect and promotes neurogenesis and differentiation of oligodendrocyte progenitor stem cells as a critical step for remyelination/ myelogenesis. Based on these properties, we hypothesized here that Bryostatin-1 is an effective treatment in multiple sclerosis.